A BRAVE NEW FRONTIER IN THE DICHOTOMOUS INDONESIAN LABOUR LAW: GIG ECONOMY, PLATFORM PARADOX AND WORKERS WITHOUT EMPLOYERS - David Tan (Mimbar Hukum, 2021)
Abstract Historical records have admitted the labour law as a curative mechanism for the disparity of bargaining power in the labour market, with contemporary theories concentrating on essential rights protection and fixing inefficiencies. The emergence of the gig economy brings turmoil despite their beneficial nature. The methodology in this study utilises a normative juridical method. The study reveals that the gig economy is not a new phenomenon, but within the context of precarious work. Recommendations were put forward as the justified necessity for a new personalised labour regulation in Indonesia based on the two general principles of statutory efficiency. Intisari Catatan sejarah telah mengakui hukum ketenagakerjaan sebagai suatu mekanisme kuratif untuk mengatasi masalah disparitas daya tawar di bursa tenaga kerja dengan teori kontemporer saat ini yang berkonsentrasi pada perlindungan hak-hak esensial serta memperbaiki inefisiensi. Munculnya gig economy membawa gejolak hukum meskipun sejatinya tetap bersifat sangat benefisial. Metodologi dalam penelitian ini menggunakan metode yuridis normatif. Studi ini mengungkapkan bahwa gig economy bukanlah fenomena baru, melainkan masih tergolong ke dalam konteks pekerjaan tidak tetap. Rekomendasi juga diajukan sebagai suatu kebutuhan yang dijustifikasi untuk memperbarui peraturan ketenagakerjaan yang lebih dipersonalisasi di Indonesia berdasarkan dua prinsip umum efisiensi hukum.